Individual and situational influences on injurious assaults against the police. Issue 2 (9th April 2018) - Barrick, Kelle; Strom, Kevin J.; Richardson, Nicholas
Abstract : Purpose: Violence against the police represents an ongoing and serious problem in the USA. In 2014, over 48, 000 law enforcement officers assaulted while on duty. Although over one in four of these resulted in injury, little is known about the conditions under which injury is likely to occur. The purpose of this paper is to provide an assessment of the individual and situational factors that predict injurious assaults against law enforcement. Design/methodology/approach: Using logistic regression, the current study analyzes data from the 2012 National Incident-Based Reporting System (NIBRS) on all assaults against the police ( n =8, 987) in order to understand, within a routine activities theoretical framework, how individual-level characteristics (i.e. officer and offender characteristics) and situational influences (i.e. assignment type, activity type, and location) predict the likelihood that an assault will result in injury. Findings: Overall, findings suggest support for a routine activities theory of violence against the police. Initiating an arrest, one-officer vehicle type, and incidents occurring on highways/roads were all more likely to result in injurious assaults against the police. Other predictors of injury include officer and offender demographics as well as the time the incident took place. Research limitations/implications: This research was unable to control for some factors that may influence the likelihood of injury such as wearing body armor. Additionally, NIBRS data are not nationally representative, which limits the generalizability of the findings. Originality/value: This is one of the first papers to use national data to examine the individual and situational factors that predict injurious assaults against law enforcement.